Climate Change Gender Action Plan (CCGAP) of the Federal Democratic Republic of Ethiopia - Tesfaye, Abonesh; Andoshe, Mohammed; Legesse, Ketema; Mulatu, Ayalneh; Ambaw, Gebermedihin; Makonnen, Brook T. (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Ethiopia faces significant challenges from climate change, with increasing temperatures, erratic rainfall, and more frequent extreme weather events. These changes threaten critical sectors such as agriculture, water resources, health, disaster risk reduction, and infrastructure, exacerbating existing vulnerabilities while posing substantial risks to sustainable development. Climate change impacts are not gender-neutral, where women and girls are disproportionately affected due to existing gender inequalities. These inequalities limit their access to resources, decision-making processes, and adaptive capacities. Women, particularly those in rural areas, endure most climate-related stresses, including food insecurity, water scarcity, and health risks. Such a threat of climate change on gender requires comprehensive and coordinated responses from national governments.